Métodos para el desarrollo de las pruebas de velocidad con los atletas de Liga Deportiva cantonal de Catamayo, provincia de Loja, período 2013 2014 - Aguinsaca Caraguay, Mario Oswaldo (2015)
This research work contains the knowledge of Methods for the Development of speed tests with athletes Liga Deportiva Cantonal de Catamayo of the Province of Loja, 2014 period; the research question revolves around the central question following the techniques used was the survey of coaches and 20 athletes interviews and the initial and final test of technical assessment of the sprint; The objectives were to determine whether the methodological processes used by coaches are suitable for the development of the sprint; and determine the time and technical-tactical foundation to develop coaches in the preparation of athletes in the sprint; and analyze whether the results obtained in the inter-cantonal championships, is due to inappropriate use of the technical and methodological development of speed tests with athletes processes; the methods used are the analytic - synthetic and descriptive; review of literature is developed according to the method variables, sports training, athletics and speed, was drafted, he applied and validated the proposed alternative workshop, therefore; after he applied the proposal, it reached the following conclusions: Coaches use unsuitable for the development of speed tests methods; Likewise the results obtained in the intercantonal, is due to misuse of the methods in the development of the sprint; as well as coaches spend little time preparing development of the sprint, and do so without any suitable method, which is reflected in the achievements in competitive sports, so it came to recommendations accordingly : that coaches should use appropriate methods; likewise, to continue using the proposal developed; and that the directors of cantonal Liga de Catamayo, select full-time coaches to devote more time in the preparation and development of athletes speed tests, appropriate methods, which improve their competitive performance